Membijaki Produk Pesantren dalam Tinjauan Fenomenologi - Fajar Indarsih; Fawait Syaiful Rahman (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2021)
Abstract Pesantren is one of the alternative institutions in continuing the process of Iqra '(reading). Iqra '(reading) can be done anywhere and on all objects. However, it is necessary to arrange a system that can bind all its sub-subs to obtain significant iqra' (reading) results. Pesantren is a form of representation of Islamic education. Exploring pesantren products means assessing the output of graduates according to the competence of graduates. Santri while in Islamic boarding schools receive complex education, not only in the field of religion but also in the areas of financial, time, and social management. Currently, the work of the students is spread all over the world. The task of the students is to continue the struggle of the teachers in conveying the truth.